Investigating the influence of job rotation on career development among production workers in Japanese companies - Mohd Zin, Md. Lazim; Mohd Shamsudin, Faridahwati; Subramaniam, Chandrakantan (Universiti Malaysia Sarawak, 2013)
The current study aims to investigate the influence of job rotation on career development. Toward this objectives, a survey was carried out amongst 209 production workers in Japanese manufacturing companies in Malaysia.Factor analysis resulted in four distinct dimensions of job rotation namely interest, business knowledge, technical knowledge and administrative knowledge, while career development resulted as unidimension. Multiple regression results indicated that all dimensions of job rotation except business knowledge influence career development. Implications of the findings, potential limitations of the study, and directions for future research are discussed.